The Impact of the U.S.-China Tariff War on Trade and Investment in Developing Countries in Disrupted Global Value Chains - Riefky, Teuku; Sabrina, Syahda; Revindo, Mohamad Dian (UI Scholars Hub, 2025)
As the world is more open and more integrated than ever, the trade war between the two largest economies, the United States (U.S.) and China, has significant and unexpected implications for multinational companies within global value chains. Since both markets are closed to each other due to the imposition of higher import tariffs, businesses have to shift their trade activities to alternative countries. Employing historical data, existing country-level data from the Global Trade Analysis Project on Value-Added (GTAP-VA), and tariffs imposed during the U.S.-China trade war, this study comprehensively examines the impacts of the trade war on global value chains, with a particular emphasis on developing countries. This study discovers that the increase in US import tariffs has a positive and statistically significant effect on the total exports of developing countries. Higher gross exports will generate higher domestic value-added (DVA) exports from developing countries, particularly those in ASEAN, as several countries compensate for reduced exports from China to the U.S. Furthermore, certain sectors or commodities are projected to benefit from the trade war, while others may experience adverse effects. The primary contributors to the increase in DVA exports are agricultural, textile, and leather products. On the other hand, high-technology manufacturing exports are likely to suffer due to the low comparative advantage of developing countries in these types of products.